Functional Outcomes Following Temporomandibular Joint Dissection Performed During Surgery for Skull Base Tumors. Issue 3 (March 2020) - Wei, Xingmei; Gao, Zhiqiang; Zhang, Tao; Zhang, Zhuhua; Tian, Xu; Zhao, Yang; Zhou, Yalin; Feng, Guodong
Abstract : Background: During skull base tumor surgery, temporomandibular joint (TMJ) dissection is commonly performed. The impact of this procedure on patients' postoperative diet and TMJ function is a matter of concern to surgeons. Methods: We reviewed the Craniomandibular Index (CMI) for 32 patients (15 men and 17 women) who underwent TMJ dissection during surgery for skull base tumors between August 2015 and May 2018. Results: Fifteen patients underwent removal of the mandibular condyle, and 17 had the condyle preserved. Twenty-one patients mainly underwent infratemporal fossa approach, and 11 underwent extended temporal bone resection. No significant difference between pre- and postoperative diet was observed in any group. Significant differences in CMI index were seen in all groups. The highest score was 0.115 of Dysfunction Index, observed postoperatively in the group that underwent condyle removal. Conclusions: For skull base tumor surgery, TMJ dissection has no significant impact on postoperative diet. Patients who underwent removal of the mandibular condyle have significantly worse postoperative TMJ function. Abstract : Supplemental Digital Content is available in the text